Aux sources de la réflexion foucaldienne sur la pastorale chrétienne antique - Jérôme Lagouanère (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
Numerous works have demonstrated the strategic role played by the study of ancient pastoral theology in the evolution of Michel Foucault’s thinking, from the question of governmentality to that of techniques of the self and subjectivity. In this paper, we examine how Foucault developed his thinking by comparing his reading notes on the subject and their use in his course Security, Territory, Population (1977-1978).